TINGKAT PENDIDIKAN DAN PENGETAHUAN IBU DALAM PEMBERIAN SUSU FORMULA BAYI USIA DIBAWAH 6 BULAN DI PUSKESMAS BANGETAYU KOTA SEMARANG - Yuliana Noor Setiawati Ulvie; Erna Kusumawati (Universitas Muhammadiyah Semarang, 2015)
UNICEF that babies fed formula have the possibility of death in the first month of his birth 25 times higher than in infants who were exclusively breastfed. Factors inhibiting the formation of awareness of parents in exclusive breastfeeding mother is ignorance about the importance of breastfeeding, how breastfeeding techniques, as well as marketing in Boost aggressively by milk producers. The research objective was to determine the level of education and knowledge in the formula feeding mothers to infants under the age of 6 months in Puskesmas Bangetayu Semarang. design of the study is retrospective analytic observation. The population in this study is a mother who has a baby under 6 months of age and fed formula milk in Semarang City Health Center Bangetayu many as 150 people. The number of samples in this study were 60 mothers with infants under 6 months of age and formula-fed at PHC Bangetayu. Analysis of the data used is the Chi-Square test. The research most respondents age is the age of 21-35 years as many as 48 respondents (80%). Age babies start eating Milk Formula is 0 months as many as 16 infants (26.7%) and education level of respondents most is basic education (elementary, middle) as many as 27 respondents (45%). Knowledge of the respondents include the category of less is 27 people (45%)Keywords: Level of education, level of knowledge, Formula Milk, Baby under 6 months